Optimization of methane production parameters during anaerobic co-digestion of food waste and garden waste. (1st November 2020) - Helenas Perin, Jessica Klarosk; Biesdorf Borth, Priscila Liane; Torrecilhas, Arthur Ribeiro; Santana da Cunha, Lucas; Kuroda, Emília Kiyomi; Fernandes, Fernando
Abstract: Anaerobic digestion is an alternative process to organic waste treatment, which enables energy production from biogas. Additionally, the volume of total waste that goes to landfills decreases, resulting in an increase in landfills lifespan. When considering different organic waste sources, food waste is highly important as it is generated and usually disposed of in large amounts. In this context, the goal of this research was to evaluate to which extent the addition of lignocellulosic waste (also known as garden waste – GW) influences the performance of food waste (FW) anaerobic digestion, focusing on process optimization as a function of the quantity and quality of the produced biogas. The experiment was conducted in two pilot-scale reactors. They were operated at the same time and contained a volume of 500 L each. Both reactors were adapted with agitators (30 rpm) and temperature controllers (36 °C). The reactor's feeding was performed in a semi-continuous process with a gradual increase in the Organic Loading Rate (OLR), from 0.24 to 0.54 kg VS m −3 d −1 . Operational control parameters, such as pH, alkalinity, VFA, and process performance, characterized by volatile solids, biogas production, and methane content, were carried out to monitor the anaerobic co-digestion. The results showed that a substitution of 20% of the food waste OLR to the lignocellulosic substrate improved both the biogas production and specific methane yield. Also, the organic material conversion efficiency, related to volatile solids (VS), reached 83%. These results indicate that the FW and GW co-digestion can be used as an alternative to organic waste treatment. The process also assists in the control of the monitoring parameters, such as pH, alkalinity and volatile fatty acids, during anaerobic digestion. Graphical abstract: Image 1 Highlights: Anaerobic digestion of food waste and it co-digestion with garden waste were evaluated. The rapid increase in organic load promoted instability in the system. Co-digestion of food waste with lignocellulosic waste improved methane production. The use of 20% in OLR of lignocellulosic waste delayed the acidification of the system.